Secondary School Students’ Perception of Science Laboratory Accident Status and Preventive Measures in Awka Education Zone - Nwune, Emmanuel Chibuike; Oguezue, Nnaemeka Kenechi; Odum, Blessing Ifeoma (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The study investigated secondary school students’ assessment of science laboratory accident status and preventive measures in the Awka Education Zone. Two research questions guided the study, and one hypothesis was tested at a .05 significance level. Methodology: The study used the descriptive survey research design. A sample of 156 public and 40 private secondary school students was used. A checklist and a questionnaire were used to collect data. The questionnaire was validated, and a Cronbach Alpha reliability test gave a coefficient of 0.86. The collected data was used to analyze mean, standard deviation, percentage, and t-tests. Main Findings: The results revealed that science laboratory accidents do not occur in secondary schools in Awka Education Zone, irrespective of school type. The study also observed no significant difference in the preventive measures against science laboratory accidents adopted by private and public secondary school students in the zone. Novelty/Originality of this study: There is limited literature in the present study’s area seeking to assess the laboratory accident status in secondary schools and the measures the students take to avert these accidents. Thus, the present study’s findings would provide background information on laboratory activities and accidents in the area of the research and preventive measures to be deployed.